Molecular modeling and docking of protease from Bacillus sp. for the keratin degradation. (January 2018) - Kandasamy, Selvam; Duraisamy, Senbagam; Chinnappan, Sudhakar; Balakrishnan, Senthilkumar; Thangasamy, Selvankumar; Muthusamy, Govarthanan; Arumugam, Sengottaiyan; Palanisamy, Srinivasan
Abstract: In this present study, the 3D structure of protease from Bacillus sp. was modeled by using modeler 9v9. The generated structure was accessed for geometrical errors and energy stability using RAMPAGE, VERFIY 3D, ERRAT and PROSA. The proteolytic nature of this modeled protease was determined by docking studies using FlexX. The kertinolytic activity was revealed by using polysacchadire sub units such as arabinose, rhamnose, galactose, and glucose; aminopeptidase activity was revealed by using amino acids like methionine, leucine, rivastigmine and also by protease inhibitor like N-carbobenzyloxy-L-alanine and 4-amidino phenyl methanesulfonyl flurode. The docking studies showed that Asp160 and Try246 residues were mainly involved in binding of all the compounds and other important amino acid residues such as His85, Asp97, Glu131, Asp160, Glu131, Glu132, Asp160, Tyr246, and His247 were involved in hydrogen bonding with the substrates. These studies also determined the substrate recognition pattern and the development of suitable protease can potentially enhance its applications in keratin degradation. Highlights: 3D models of protease from Bacillus sp. have been built. Prediction of active sites of the substrates. Active site characterization based on docking studies of the substrates.